ANDRAGOGY APPROACH IN ACCELERATION OF STUNTING REDUCTION: SOCIAL SUPPORT AND COMMUNITY PARTICIPATION ANALYSIS - Ayub , Daeng; Putra, M. Jaya Adi; Karwati, Lilis; Muryanti (International Journal of Educational Best Practices, 2024)
This study examines the role of the andragogical approach, social support, and community participation in accelerating stunting reduction in Sibuak Village, Tapung District, Kampar Regency. The objectives of the study are to assess the levels of these three factors and to analyze their influence on stunting reduction efforts. Specifically, the study aims to (1) evaluate the extent of the andragogical approach applied in stunting reduction, (2) measure the level of social support provided, (3) assess the level of community participation, and (4) determine the effects of social support and community participation on the andragogical approach in the context of stunting reduction. To do so, this study employs a quantitative design with a sample of 126 fertile couples from a population of 183 in the village. Data were analyzed using descriptive statistics to determine central tendencies and inferential statistics to explore relationships between the variables. The results show a significant positive influence of social support on the andragogical approach, accounting for 75.1% of the variance. Community participation also had a significant positive influence, explaining 73.7% of the variance. Additionally, combined social support and community participation had a significant impact on the andragogical approach, with a total effect of 75.3%. The findings suggest that enhancing social support and encouraging community participation are crucial for strengthening the andragogical approach in reducing stunting. These insights can inform policymakers and health practitioners in designing more effective stunting reduction programs.